A manifestação do sagrado na Noite dos Tambores Silenciosos - Silva Júnior, Luiz Justino da (2009)
Any human experience can become sacred and even go continuing going externally continue in its profane expression. This sacred character comes out to it human experience from the mystery touch that it the above mentioned human experience hides within itself. This mystery can enclose beauty or ugliness, goodness or wickedness, safety or sin, angles or devils, temples or street. The sacred one produces, accomplishes a certain transformation in the worldly things, turning them into a reality wholly different from an analyzing, departing from an anthropological perspective, the hidden hierophany, contacted and reworked out from Noite dos Tambores Silenciosos i. e: Night of the Silent Drums in great attempt of understanding and developing this process.